Contribution on the knowledge of Sesiidae in the Thracian Region of Türkiye (Insecta: Lepidoptera) - Feza Can; Serdar Akar; Theo Garrevoet (SHILAP)
Sesiidae (Lepidoptera) is an important family which includes economically pest species in a variety of agricultural  products in the order. In this study it was aimed to contribute to the Sesiidae species in the Thracian region of Türkiye by using pheromone traps and netting in 2021. In the study 11 Sesiidae species belonging to seven genera were determined: Microsphecia brosiformis (Hübner, [1813]), M. tineiformis (Esper, [1789]), Negotinthia myrmosaeformis (Herrich-Schäffer, [1846]), Paranthrene tabaniformis (Rottemburg, 1775), Synanthedon myopaeformis (Borkhausen, 1789), S. vespiformis (Linnaeus, 1761), Bembecia ichneumoniformis ([Denis & Schiffermüller], 1775), B. scopigera (Scopoli, 1763), Pyropteron minianiformis (Freyer, 1843), P. triannuliformis (Freyer, 1843) and Chamaesphecia doryceraeformis (Lederer, 1853). M. tineiformis, which is not common in Türkiye and was recorded for the first time from the Thracian region (European part) of Türkiye.